(untitled) (Proceedings of Southern Federal University. Philology, 2012)
Dmitrova A.V. Keywords: the Russian immigration, Poplavsky, motif, lost motherland. The article is devoted to the consideration of the lost motherland motif in Boris Poplavsky’s novel “Apollo Unformed” and its relation to the other motifs of the text. They are the existential phenomena of loneliness, abandonment of a person in the world, homelessness. Being connected to each other, they are interwoven into the motivic structure of the novel. In this context, the motif of the lost homeland is the starting point for considering the structure of the novel unity as a whole.